Geological Position of Rare-Metal Pegmatites of the Laghman Granitoid Complex, Afghanistan - Evdokimov A. N.; Yosufzai Ataullah (Russian Journal of Earth Sciences, 2025)
Rare-metal pegmatites containing industrial concentrations of lithium, tantalum, niobium, cesium, beryllium, and tin are becoming increasingly important as raw material objects for the production of electrical equipment, batteries, and electronics. In this context, studying the patterns of their geological and structural setting is highly relevant, as it allows the identification of prospecting criteria to discover new resource-bearing sites and expand the reserves of known rare-metal pegmatite deposits in the Nuristan zone of northeastern Afghanistan. Here, pegmatite fields are spatially associated with the Oligocene granites of the Laghman complex and are located in the provinces of Afghanistan: Nuristan, Kunar, Laghman, Kabul, Nangarhar, Kapisa, Panjshir, and Badakhshan. They have been known since ancient times as sources of gemstones and mica. The Laghman granitoid complex is characterized by the sequential intrusion of three intrusive phases: 1 – diorites, quartz diorites, granodiorites, and plagiogranites; 2 – porphyritic biotite granites, amphibolebiotite granites, and granodiorites; 3 – two mica and biotite granites, granite porphyries, aplite, and pegmatoid granites. Rare-metal pegmatites are confined to the third phase of the Laghman granite intrusion. Here, granites are characterized by heterogeneous texture, from granoblastic to granitic, with fragments of aplitic and poikilitic texture. The host rocks of pegmatites are Triassic phyllite-like quartz-mica schists and Proterozoic gneisses and quartzites. Additionally, pegmatites are found within intrusive rocks, specifically within gabbro-diorites massifs of the Nilaw complex. The morphology of the bodies of rare-metal pegmatites is diverse. Veins with swells and plate-like bodies predominate, while lens-shaped forms and irregularly oriented veins are less common. The thickness of pegmatite veins ranges from 1 to 60 m, and their length varies from tens of meters to 2–5 km. It is assumed that the formation of the Laghman granitoid complex is a consequence of the collision of the Indian continent with Eurasia.